Clinical diagnosis of patellofemoral disorders : the role of bioengineering - Leal, Ana (2013)
The concept of bioengineering perfectly meets the purpose of building a bridge across two distinct but complementary areas: engineering and health sciences. The active cooperation of these scientific domains is the key solution to solve daily clinical problems. In fact, most of the medical devices currently available derive from last century engineering scientific discoveries. Thus, the biomedical engineer intervention plays an important and crucial role on the medical field evolution. In this work special emphasis is given to the patellofemoral (PF) joint due to the high complexity of this articulation and its pathological cases. There is an ambiguous definition of PF disorders, as long as they share a common thread with and have impact on nearly all knee conditions. Additionally, its multifactorial etiology intensifies the misunderstanding of its physiopathology, compromising its diagnosis, which de per se is actually performed in a non-rigorous, accurate nor reliable way. This research aims at analyzing the first steps of a main goal: develop a standard precise methodology to aid on the diagnosis of PF articulation. Starting by the description of the state of the art, this paper discusses the project methodology initially applied and highlights the future prospects for this work.